The system of nonlinear adaptive control for wind turbine with DFIG - Medvedev, Mikhail; Mazalov, Andrey (EAI Endorsed Transactions on Energy Web, 2014)
This paper presents a problem solution of the stable voltage generating in the changing terms of environment for the double-fed induction generator (DFIG). For this, in nonlinear multivariable systems, such as mathematical model of DFIG, the method of observer’s synthesis for external, parametric and structural disturbances was used. This allows, on the basis of disturbances approximation, to carry out an evaluation under conditions of uncertainty, leading to disturbances adaptation with a priori unknown structure. The work presents a synthesis method of control system, allowing to solve indicated problem. Stand-alone wind turbine used as a power plant with DFIG. The control system uses the original nonlinear mathematical model of the DFIG in rotating “dq” coordinates, taking into account non-linear changes in the parameters. To confirm the effectiveness of the problem solution, mathematical computer model was developed. The paper also presents the results of full-scale simulation.